1999
DOI: 10.1159/000008701
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Effects of Second-Generation Calcium Channel Blockers on Experimental Heart Transplantation

Abstract: The administration of second-generation calcium channel blockers (CCBs) to counteract the adverse effects of conventional immunosuppression gains more and more acceptance. Since these newly developed molecules differ in their chemical structure and possess specific pharmacokinetic profiles, we hypothesized that exposure to clinically relevant concentrations may have a significant immunomodulatory potential. The effects of various second-generation CCBs, felodipine, amlodipine, mibefradil and clentiazem, on car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Transmembrane calcium movement plays a critical role in lymphocyte function, and numerous investigators have demonstrated that diltiazem inhibits lymphocyte functions and depresses the immune response. [36][37][38] We speculate whether through any of these mechanisms diltiazem may explain the protective effect against CAV that we have found in our analysis.…”
Section: Discussionmentioning
confidence: 67%
“…Transmembrane calcium movement plays a critical role in lymphocyte function, and numerous investigators have demonstrated that diltiazem inhibits lymphocyte functions and depresses the immune response. [36][37][38] We speculate whether through any of these mechanisms diltiazem may explain the protective effect against CAV that we have found in our analysis.…”
Section: Discussionmentioning
confidence: 67%
“…1, 5-Benzothiazepines having a heterocyclic group at the different position of the ring have been found to be of psychopharmacological use. Various other useful properties [9][10][11][12][13][14][15][16][17][18][19][20] have been shown by 1, 5-Benzothiazepines and different compounds having heterocyclic function have been synthesized. The biodynamic nature of 1, 5-benzothiazepine derivatives led to the current synthesis of 1,5-benzothiazepines having various substituents at positions 2, 4 and 8, which may prove to be medicinally potent.…”
Section: Introductionmentioning
confidence: 99%
“…1, 5-Benzothiazepines having heterocyclic group at different position of ring have been found to be of psychopharmacological use. Various other useful properties [9][10][11][12][13][14][15][16][17][18][19][20] has been shown by 1, 5-benzothiazepines and different compounds having heterocyclic function have been synthesized.…”
Section: Introductionmentioning
confidence: 99%